1997
DOI: 10.1006/jevp.1997.0059
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Performance and Mood Effects of Information About Lighting and Fluorescent Lamp Type

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 16 publications
0
31
0
1
Order By: Relevance
“…Similarly, Luckiesh and Moss [46] determined that lighting and its quality related positively to student test scores. Veitch [64] , however, argued that regardless of the quality and quantity of lighting it had no effect on the mood or performance of students. In a different but related study, Knez and Kers [44] explored the effect of lighting and gender to find that females were more perceptive to light than males.…”
Section: Effects Of Air Conditioning and Lighting On Student Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Luckiesh and Moss [46] determined that lighting and its quality related positively to student test scores. Veitch [64] , however, argued that regardless of the quality and quantity of lighting it had no effect on the mood or performance of students. In a different but related study, Knez and Kers [44] explored the effect of lighting and gender to find that females were more perceptive to light than males.…”
Section: Effects Of Air Conditioning and Lighting On Student Achievementmentioning
confidence: 99%
“…Correlational research Alassaf [3] A survey design was judged to be the most appropriate for the present study for a number of reasons. According to Reference [64,34] survey studies allows researchers to obtain information about the case, facts, activities, phenomena, moral, personal experiences, behaviour and answers to events. Questionnaires also offer the advantage of allowing sufficient time for the respondents to reflect on their answers.…”
Section: Research Design Data Collectionmentioning
confidence: 99%
“…Two cognitive processes, demand characteristics and reactance, were offered as possible explanations for the reactions to the two information sets; alternatively, providing information about lighting might increase arousal sufficiently to affect task performance. However, Veitch (1997) conducted a replication study that found neither information sets nor lamp type effects on performance or mood, despite a larger sample size, double-blind experimental control, and a more vivid information set using a video presentation. If the anecdotal reports about beneficial changes following FSFL installation illustrate the action of expectancies created by advertising or promotional material, the process by which this occurs is difficult to create in a laboratory setting.…”
Section: Cognitive Mediators 521 Expectationsmentioning
confidence: 99%
“…Other research groups have not found lamp type effects on mood in laboratory and field experiments that compared a variety of fluorescent lamp types (Bartholomew 1975;Berry 1983;Boray et al 1989;Kuller and Wetterberg 1993;Veitch et al 1991;Veitch 1997). FSFL did not produce improved mood in any of these experiments, which include both within-subjects and double-blind between-subjects designs and a range of exposure times (e.g., field studies with 14 working days' exposure to each type [Berry 1983]; laboratory studies from 2 hours [Veitch 1997] to one working day in length [Kuller and Wetterburg 1993]).…”
Section: Affectmentioning
confidence: 99%
See 1 more Smart Citation